Severe Adaptive Immune Suppression May Be Why Patients With Severe COVID-19 Cannot Be Discharged From the ICU Even After Negative Viral Tests - Zhou, Yue; Liao, Xuelian; Song, Xiangrong; He, Min; Xiao, Fei; Jin, Xiaodong; Xie, Xiaoqi; Zhang, Zhongwei; Wang, Bo; Zhou, Chenliang; Kang, Yan; Zhang, Wei (Frontiers in Immunology, 2021)
During the COVID-19 pandemic, a phenomenon emerged in which some patients with severe disease were critically ill and could not be discharged from the ICU even though they exhibited negative viral tests. To explore the underlying mechanism, we collected blood samples from these patients and analyzed the gene expression profiles of peripheral immune cells. We found that all enrolled patients, regardless of changes in genes related to different symptoms and inflammatory responses, showed universally and severely decreased expression of adaptive immunity-related genes, especially those related to T/B cell arms and HLA molecules, and that these patients exhibited long-term secondary infections. In addition, no significant change was found in the expression of classic immunosuppression molecules including PD-1, PD-L1, and CTLA-4, suggesting that the adaptive immune suppression may not be due to the change of these genes. According to the published literatures and our data, this adaptive immunosuppression is likely to be caused by the “dysregulated host response” to severe infection, similar to the immunosuppression that exists in other severely infected patients with sepsis.